Extensively Drug-Resistant Neisseria gonorrhoeae Strain, Canada - Brigitte Lefebvre; Irene Martin; Robyn Thorington; Julian Gitelman; Andrew Bui-Nguyen; Claude Fortin; Judith Fafard (Emerging Infectious Diseases)
We identified a case of extensively drug-resistant (ceftriaxone- and cefixime-resistant and high-level azithromycin-resistant) Neisseria gonorrhoeae in Canada. The strain harbors the penA 60.001 allele, which includes the A311V and 23S rRNA A2059G single-nucleotide polymorphisms associated with high-level azithromycin resistance. The infection was likely acquired during travel in Cambodia.